Pre and Post Merger Effect on Physical Performance of Banking Industry in India - Gupta , Sonu V; Chawla, Prakash; Harkawat , Sandhya (Gyan Management Journal, 2012)
Over the past decades changes in regulation, technological advancement, competitive trends and disintermediation have a/I led to large scale banking sector consolidation all over the world. Since 1991, the process of Liberalization and Globalization initiated by the Government has influenced the functioning and Governance of the Indian banking sector.The present paper aims at empirically investigating the impact of M&As on physical performance of Merged Banks, A sample of six banks viz., BOB, PNB, OBC, HDFC, ICICI and CBOP were considered for the purpose of Physical analysis., an attempt is made by selecting the physical parameters to find out the synergy of merged banks. Variables under study are Deposit,Advances, business, No. of employees, No. of Branches and profit of the Banks. A Pre and Post Merger analysis is been done to find out the effect of merger on the banks. Analysis is done by comparing Average means of Pre and post merger period. Further corelation and regression analysis is done by taking profit as dependent variables and others as independent variables to find out whether independent variables have an impact on dependent variables in pre and post merger period. The result shows that mean comparison of deposits, advance,business, No. of Branches and profit had increased in post merger period giving a positive impact of merger in banks. No. of employees in reduce in post merger period of the banks hence reducing the cost.Regression t-test shows significant level at 0.05%, further analysis showed that both merger of private banks with private banks and merger of private bank with public bank are significant, but correlation of private banks with private banks is more than private bank with public banks.
Keywords: Physical Performance; Mergers and Acquisitions; Private and Public Sector Banks